Automatic 3D garment positioning based on surface metric. (May 2017) - Tisserand, Yvain; Cuel, Louis; Magnenat‐Thalmann, Nadia
Abstract: Positioning virtual garments onto a 3D avatar is known to be a time‐consuming process. This task is usually done manually if the proportion of the garment needs to be kept during the process for a fitting purpose. The positioning of the garment is currently the main limitation to propose a fully automatic virtual try‐on application. This paper presents an automatic method based on surface energy minimisation that allows fully automatically positioning of a 3D virtual cloth without deformation of the patterns. The minimum of surface energy is reached by animating the humanoid avatar. Humanoid joints are manipulated to place a 3D avatar into the virtual garment. The proposed method, as well as its implementation, is described in this paper.